Issues in Private-Sector Finance in Israel - Hemmings, Philip (OECD Economics Department Working Papers, 2011)
The 2008-09 global financial crisis did not result in the failure of any major financial institution in Israel, but it did reveal vulnerabilities in the non-banking sector . particularly in the corporate-bond market. Conservative regulation of the banking sector helped this segment avoid a financial meltdown, and low loan-to-value ratios in mortgage lending are undoubtedly helping limit the pace of house-price increases. Nevertheless, as elsewhere, capital requirements and stress tests for banks have been ramped up. Also the identification and monitoring of systemic risks and macro-prudential problems has intensified. In the Israeli context somewhat unusual issues arise from the control of most of Israel.s major financial institutions by family-based business groups that have significant interests in non-financial sectors of the economy. This close link between the financial and non-financial sectors generates potential risks to financial stability, and it is a key issue in a wider debate about the relative merits of the business groups in terms of competition and control in the economy. This Working Paper relates to the OECD 2011 Economic Survey of Israel (www.oecd.org/eco/surveys/Israel)